Self-Care Practices among Patients with Diabetes Mellitus - Roka, Tara; Sherpa, Dawa Futi; Basnet, Asmita (Journal of Nepal Health Research Council, 2025)
Background: Diabetes Mellitus (DM) requires continuous self-care practices to prevent acute and chronic complications. With the possibility of several physical and psychological complications alongside affecting the social aspect of life, improving self-care is highly important in patients with DM. The aim of this study was to measure self-care practices among patients with DM and factors associated with inadequate self-care. Methods: Information on self-care practices was collected using the summary of Diabetes Self-care Activities (SDSCA) in a hospital based cross-sectional study among 345 participants selected through sequential sampling. Data was analysed using descriptive and inferential statistics and results were presented with proportions and odds ratios with a 95% confidence interval (CI). Results: We found that 30.7% of the participants had adequate self-care practices across all domains. A fairly substantial proportion had adequate self-care in diet and exercise related care with 87.5% and 65.5%, respectively. However, with foot care and blood sugar monitoring related care only a small to negligible proportion had an adequate level of self-care. Multivariate analysis showed that participants aged 65 years and above had higher odds of having inadequate self-care practices (aOR:5.20; 95%CI: 2.20-12.33); and those with diabetes for more than five years had twice the odds (aOR:2.10; 95%CI: 1.15-3.83) of having inadequate self-care. Conclusions: A large proportion of the participants had inadequate self-care practices, and this was even poorer in domains of foot care and blood sugar monitoring. Age of the participants, marital status and duration of illness were factors independently associated with inadequate self-care. Targeted behavior change interventions for patients visiting hospitals and health care centers in Nepal could improve self- care practices among patients with DM. Keywords: Diabetes mellitus; hospital; Kathmandu; Nepal; self-care